2023
DOI: 10.1097/inf.0000000000003924
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Clinical Phenotype of Multisystem Inflammatory Syndrome in Children After Two SARS-CoV-2 Pandemic Waves: A Croatian Prospective Nationwide Study

Abstract: This prospective nationwide study in Croatia (March 1, 2020-December 31, 2021) embraced 121 children with multisystem inflammatory syndrome. Incidence rates, disease course and outcomes were similar to those reported from other European countries. The severe acute respiratory syndrome coronavirus 2 virus Alpha strain appeared associated with a higher propensity to result in multisystem inflammatory syndrome in children than the Delta strain but did not appear related to disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The variations inherent in such illnesses have become more apparent; therefore, several clinical definitions have emerged. Overall, it is suggested that very few SARS-CoV-2-infected children suffer from MIS-C [ 59 , 78 , 79 ]. Among all pediatric MIS-C in 2 of the latter studies, some 1.7%–2.6% were <1 year of age.…”
Section: Covid-19 Among Infantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variations inherent in such illnesses have become more apparent; therefore, several clinical definitions have emerged. Overall, it is suggested that very few SARS-CoV-2-infected children suffer from MIS-C [ 59 , 78 , 79 ]. Among all pediatric MIS-C in 2 of the latter studies, some 1.7%–2.6% were <1 year of age.…”
Section: Covid-19 Among Infantsmentioning
confidence: 99%
“…The similarities to Kawasaki disease and toxic shock syndrome continue to be explored, and rightfully so [ 155 ]. Some data suggest the possible difference in MIS-C incidence depending on the SARS-CoV-2 strain dominance [ 79 ].…”
Section: Controversy Regarding Infantsmentioning
confidence: 99%